Decoding the Disciplines as a Hermeneutic Practice. (June 2017) - Yeo, Michelle
Abstract : This chapter argues that expert practice is an inquiry that surfaces a hermeneutic relationship between theory, practice, and the world, with implications for new lines of questioning in the Decoding interview.